Supporting Mobile Web Augmentation by End Users - Bosetti, Gabriela Alejandra (2017)
This article presents MoWA Authoring, an End User Development platform supporting the improvement of existing –usually third party– Web applications with mobile features. This enhancement is carried out by the addition of specific behaviours, mostly dependent on context values. The tool assists the user in the construction of applications by easily selecting the components that fit his needs. A series of forms allows selecting sensors, context values of interest and digital counterparts to define an augmentation layer. The latter is composed of augmentation units, called augmenters, which are configurable through widgets that can be placed over the presentation layer of any Web application.